Ethnographical research of the Folk Costume of Hutsulshchyna - Білей-Рубан, Н. В.; Сєдоухова, Є. В.; Петрусь, Л. М.; Полуда, С. Н. (Art and Design, 2019)
Comprehensive study and research of the creative achievements of Hutsulshchyna, namely the constituent parts of Hutsul art, the Hutsul ceremonial and everyday outfits and its decor on the basis of the development of museum exhibits, in particular the Museum of Applied Arts of Transcarpathia at the Mukachevo State University, as well as its own sources. The research was based on the methods of comparative analysis, methods of comparative-historical reconstruction of folk costume, and art criticism analysis. Specific types of Hutsul art are systematized on the basis of analysis of the ethnographic region, which covers the Hutsulshchyna. The elements of the Hutsul male and female costume were selected and defined, with a generalization of its components and with a clear set of features of decoration and decoration in accordance with specific areas of Hutsulshchyna. The course of studying and researching the Hutsul folk costume as a theoretical and methodological basis for the design of modern clothing with ethnoelements is proposed. The scientific novelty consists in characterizing the constructive arrangement of the components of the Hutsul men’s and women’s clothing, its elements of decoration and manufacturing methods as the basis for the artistic design of products with the ethno designer component. This approach made it possible to present the features of the Hutsul costume and to further explore the specifics of its creation, which in turn would facilitate the use of the results obtained in the methodology of artistic design of industrial products on the basis of ethnomotypes.